Women's right: the qur'anic ideals and contemporary realities - Akhmetova, Elmira (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2015)
This article is a study of the rights of women in Islam in comparison with the status of women in the contemporary Muslim world. Men and women in Islam, regardless of their age, social class and education, are equal as citizens and individuals, but not identical, in their rights and responsibilities. It suggests that, in the early age of Islam, women were given full confidence, trust and high responsibilities in leadership, educational guidance and decisionmaking. But this Islamic empowerment of women bears little relation to the real condition of women in modern Muslim societies. Women suffer the most in the MENA and other conflict-ridden regions from insecurity, domestic abuse, low access to education and medical care. The absence of good governance also results in gender inequality and violation of the rights of women. Without good governance, the status of women is not likely to improve. Muslim women have a potential to play a fundamental role in curbing corruption, social ills, violence and crime in the Muslim world. Therefore, in order to achieve stability and prosperity, the government must ensure a platform for women to participate in decision-making and benefit from the rights they are accorded in Islam.